2009
DOI: 10.1523/jneurosci.1294-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dual Adaptation Supports a Parallel Architecture of Motor Memory

Abstract: Although our understanding of the mechanisms underlying motor adaptation has greatly benefited from previous computational models, the architecture of motor memory is still uncertain. On one hand, two-state models that contain both a fast-learning-fast-forgetting process and a slow-learning-slow-forgetting process explain a wide range of data on motor adaptation, but cannot differentiate whether the fast and slow processes are arranged serially or in parallel and cannot account for learning multiple tasks simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
235
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(263 citation statements)
references
References 42 publications
(90 reference statements)
8
235
8
Order By: Relevance
“…Different variations of the SSM have been recently suggested to explain adaptation and savings during force field (Donchin et al 2003;Smith et al 2006), object rotation (Ingram et al 2011), and visuomotor (Lee and Schweighofer 2009;Zarahn et al 2008) perturbations. Most of these models assume linear time invariant (LTI) properties of the parameters (Donchin et al 2003;Ingram et al 2011;Lee and Schweighofer 2009;Smith et al 2006) while the rest model assumes varying parameters that change with experience (Berniker and Kording 2011;Zarahn et al 2008). All of these error-based models suggest that trial-by-trial adaptation occurs by updating the appropriate internal models (i.e., states) to reflect the behavior of the perturbation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different variations of the SSM have been recently suggested to explain adaptation and savings during force field (Donchin et al 2003;Smith et al 2006), object rotation (Ingram et al 2011), and visuomotor (Lee and Schweighofer 2009;Zarahn et al 2008) perturbations. Most of these models assume linear time invariant (LTI) properties of the parameters (Donchin et al 2003;Ingram et al 2011;Lee and Schweighofer 2009;Smith et al 2006) while the rest model assumes varying parameters that change with experience (Berniker and Kording 2011;Zarahn et al 2008). All of these error-based models suggest that trial-by-trial adaptation occurs by updating the appropriate internal models (i.e., states) to reflect the behavior of the perturbation.…”
Section: Methodsmentioning
confidence: 99%
“…Initial attempts to model adaptation to an external perturbation were based on state space models (SSMs) composed of a fast and one or multiple slow processes (Lee and Schweighofer 2009;Smith et al 2006). However, these linear multiple-rate SSMs could not explain savings that occur after a prolonged period of washout (Krakauer et al 2005;Zarahn et al 2008) and across days (Robinson et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We modeled the motor learning process using the state space model (Thoroughman and Shadmehr, 2000;Wainscott et al, 2005;Lee and Schweighofer, 2009;Nozaki and Scott, 2009), consisting of N primitives that encode the movement directions of both arms as g( r , l ), where r and l are the movement directions of the right and left arms, respectively (see Fig. 3A).…”
Section: Methodsmentioning
confidence: 99%
“…Other investigators have found cases in which learning could not be described in terms of exponential decay functions, where "no meaningful value for τ could be calculated" and "the problem could not be alleviated by using double exponentials [6]." However, others suggest two [7] (Smith and Shadmehr) or more [8] (Schweighofer) learning processes. Our data suggests immediate performance changes in the error-augmented group when compared to the control group.…”
Section: Sharpmentioning
confidence: 99%